The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/bjh.13318
|View full text |Cite
|
Sign up to set email alerts
|

Entinostat, a novel histone deacetylase inhibitor is active in B‐cell lymphoma and enhances the anti‐tumour activity of rituximab and chemotherapy agents

Abstract: Summary Histone deacetylases (HDACs) inhibitors are active in T-cell lymphoma and are undergoing pre-clinical and clinical testing in other neoplasms. Entinostat is an orally bioavailable class I HDAC inhibitor with a long half-life, which is under evaluation in haematological and solid tumour malignancies. To define the activity and biological effects of entinostat in B-cell lymphoma we studied its anti-tumour activity in several rituximab-sensitive or -resistant pre-clinical models. We demonstrated that enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…That being said, further preclinical analyses are necessary to assess the tolerability and efficacy of RV in combination with clinically relevant HDACi. In fact, although AR-42 as a single agent in our trial (NCT 01798901) was well tolerated in 26 patients with hematopoietic diseases, including MM, it displayed a shorter half-life (4–56hrs, C max 0.3–1.2μM) compared to Entinostat (33). On the other hand, LBH has been recently approved for the treatment of MM and may result in the most valuable companion drug for RV therapy in relapse patients.…”
Section: Discussionmentioning
confidence: 81%
“…That being said, further preclinical analyses are necessary to assess the tolerability and efficacy of RV in combination with clinically relevant HDACi. In fact, although AR-42 as a single agent in our trial (NCT 01798901) was well tolerated in 26 patients with hematopoietic diseases, including MM, it displayed a shorter half-life (4–56hrs, C max 0.3–1.2μM) compared to Entinostat (33). On the other hand, LBH has been recently approved for the treatment of MM and may result in the most valuable companion drug for RV therapy in relapse patients.…”
Section: Discussionmentioning
confidence: 81%
“…Although the underlying mechanisms are not clear, HDAC inhibitors are wildly used in combination with chemotherapeutic agents to enhance anticancer activity [4649]. As a selective class I HDAC inhibitor, entinostat has shown promising efficacy in the treatment of B cell lymphomas [39,40,50]. Our previous studies also revealed that entinostat in combination with melphalan or bendamustine synergistically induced growth inhibition and apoptosis in MM cells [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…In clinic testing, entinostat shows benefit in estrogen receptor-positive breast cancer [32], non-small cell lung cancer [33], melanoma [34], and some T cell lymphoma [3538]. Its combination with chemotherapy demonstrates enhanced efficacy in B cell lymphoma [37,3941]. In the current study, we have attempted to seek the combinatorial effects of cladribine and entinostat on cell proliferation and survival in MM cells, and explore the underlying mechanism that cladribine combined with entinostat serves as a novel therapeutic strategy against MM.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of 177 Lu‐lilotomab used was approximately 50% of the maximum tolerated dosage (MTD) and was chosen so that the therapeutic effect of the single treatment was suboptimal in order to be able to detect an increased effect of the combination with rituximab. The same thinking guided the choice of rituximab dosage which was chosen based on published data on similar animal models . Nine to ten mice were used per group.…”
Section: Methodsmentioning
confidence: 99%
“…The same thinking guided the choice of rituximab dosage which was chosen based on published data on similar animal models. 31,32 Nine to ten mice were used per group. Mice were administered with the first treatment on day 8; study day 0 was set at injection of tumour cells.…”
Section: Therapy Studiesmentioning
confidence: 99%